PARTIAL HYSTERECTOMY IN RINGWOMB CAUSING UTERINE NECROSIS IN A GOAT - AHUJA, ANKIT KUMAR; KUMAR SINGH, ASHWANI; SINGHAL, SUMIT; KHIANGTE, LALCHHANHIMA; JAN, FIZA (The Indian Journal of Animal Reproduction, 2020)
Cesarean section is a life-saving operative technique, helpful in saving the life of dam as well as fetus if done at appropriate time to relieve dystocia. Incidence of dystocia in small ruminants is usually low. Both maternal and fetal factors contribute to the dystocia. Maternal dystocia commonly relates to incomplete cervical dilatation (ringwomb), narrow birth canal, uterine inertia and fetal factors associated with dystocia are malposition/presentation, feto-pelvic disproportion/fetal oversize, and fetal malformation. Present case discusses about caesarean section in a goat occurring due to ring-womb and partial hysterectomy performed was thereafter.